Unexpected arboviruses found in an epidemiological surveillance of acute tropical febrile syndrome in the department of Meta, Eastern Colombia - Liliana Sánchez-Lerma; Andres Rojas-Gulloso; Jorge Miranda; Vanesa Tique; Luz Helena Patiño; Derly Rodriguez; Verónica Contreras; Alberto Paniz-Mondolfi; Norma Pavas; Juan David Ramírez; Salim Mattar (Elsevier, 2024)
Background: Nonspecific acute tropical febrile illnesses (NEATFI) are common in the Latin American tropics. Dengue, Chikungunya, Zika, Mayaro, and Usutu, among others, can coexist in the American tropics. This study aimed to surveil the arboviruses that cause| acute febrile syndrome in patients in the Meta department, Colombia. Methods: Between June 2021 and February 2023, an epidemiological surveillance study was conducted in the Llanos of the Meta department in Eastern Colombia. Results: One hundred patients in the acute phase with typical prodromal symptoms of NEATFI infection who attended the emergency department of the Villavicencio Departmental Hospital were included. ELISA tests were performed for Dengue, Usutu, Chikungunya, and Mayaro. RT-qPCR was performed to detect the arboviruses Usutu, Dengue, Zika, Mayaro, and Oropouche. The seroprevalence for the Chikungunya, Mayaro, and Usutu viruses was 41 % (28/68), 40 % (27/67), and 62 % (47/75), respectively. Seroconversion for Chikungunya was observed in one patient; two seroconverted to Mayaro and one to Usutu. The NS5 gene fragment of the Usutu virus was detected in nine febrile patients. RT-qPCR of the remaining arboviruses was negative. The clinical symptoms of the nine Usutu-positive patients were very similar to those of Dengue, Chikungunya, Zika, and Mayaro infections. Conclusions: The pervasive detection of unexpected viruses such as Usutu and Mayaro demonstrated the importance of searching for other viruses different from Dengue. Because Usutu infection and Mayaro fever have clinical features like Dengue, a new algorithm should be proposed to improve the accuracy of acute tropical fevers.